2000
DOI: 10.1046/j.1460-9568.2000.00914.x
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal and vascular localization of histamine N‐methyltransferase in the bovine central nervous system

Abstract: Histamine N-methyltransferase (HMT) (EC 2.1.1.8) plays a crucial role in the inactivation of the neurotransmitter histamine in the CNS. However, the localization of HMT remains to be determined. In the present study, we investigated immunohistochemical localization of HMT in the bovine CNS using a polyclonal antibody against bovine HMT. The HMT-like immunoreactivity was observed mainly in neurons. Strongly immunoreactive neurons were present in the oculomotor nucleus and ruber nucleus in the midbrain, the faci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 44 publications
(94 reference statements)
0
20
1
Order By: Relevance
“…It has been demonstrated that HMT distribution in brain is not homogeneous (Bischoff and Korf, 1978;Nishibori et al, 2000) and thus, the effect of reserpine on HA catabolism in hypothalamus and cortex of rats might depend on the distribution and activity of HMT.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that HMT distribution in brain is not homogeneous (Bischoff and Korf, 1978;Nishibori et al, 2000) and thus, the effect of reserpine on HA catabolism in hypothalamus and cortex of rats might depend on the distribution and activity of HMT.…”
Section: Discussionmentioning
confidence: 99%
“…Histaminergic innervation of the HMN has been demonstrated in the rat (Panula et al, 1989) and guinea pig (Bouthenet et al, 1988). The HMN has also been shown to contain high amounts of HA Nmethyltransferase (Nishibori et al, 2000), which plays a crucial role in HA inactivation. HA neurons display wakingspecific discharge, becoming completely silent at sleep onset (Sakai et al, 1990;Takahashi et al, 2006;Vanni-Mercier et al, 2003).…”
Section: Ha and Gg Muscle Activitymentioning
confidence: 99%
“…Stored histamine in specialized secretory vesicles is released by depolarization stimuli both in vivo and in vitro [20,21,23,36,40] . Inactivation of released histamine is believed to proceed by its direct enzymatic transformation to N -methylimidazole acetic acid through N -tele-methylation by histamine N -tele-methyltransferase (EC 2.1.1.8) and oxidative deamination by monoamine oxidase B (EC 1.4.3.4) and aldehyde dehydrogenase (EC 1.2.1.3) [7,16,26,42] . Histamine is transported into both neuronal and glial cells, and inactivated in these cells [16] .…”
mentioning
confidence: 99%
“…Inactivation of released histamine is believed to proceed by its direct enzymatic transformation to N -methylimidazole acetic acid through N -tele-methylation by histamine N -tele-methyltransferase (EC 2.1.1.8) and oxidative deamination by monoamine oxidase B (EC 1.4.3.4) and aldehyde dehydrogenase (EC 1.2.1.3) [7,16,26,42] . Histamine is transported into both neuronal and glial cells, and inactivated in these cells [16] . However, the transport system of neuronal histamine is still unclear, although there was a paper on uptake of [ 14 C]histamine into rat synaptosomes [43] .…”
mentioning
confidence: 99%